A world turned upside down: Social hierarchies and a new history of egalitarianism. Issue 4 (5th March 2014) - Anderson, Elizabeth; Jackson, Ben; Phillips, Anne
Abstract : Elizabeth Anderson traces the history of egalitarian ideas as they have grown out of grassroots movements focused on overcoming entrenched social hierarchies. In reply, Ben Jackson andAnne Phillips engage with this relational account, particularly in a British context where distributional concerns are high on the political agenda.